WORKSHOP SERIAL PENULISAN KARYA ILMIAH DAN MANAJEMEN PUBLIKASI SEBAGAI UPAYA PROFESIONALISME PPPK DAN CPNS - Muzaki, Muhamad Azka; Purnomo, Raihan Ade; Fatir, Luthfi Ikmal; Rohmatunisa, Nasya; Putri, Amanda; Rohman, Mazda Muhammad Fadlur; Masruroh, Siti Ummi (Jurnal Pengabdian Masyarakat AbdiMas, 2025)
AbstractDeveloping the professionalism of lecturers and academic staff, particularly Government Employees with Work Agreements (PPPK) and Civil Servant Candidates (CPNS), is crucial for university performance. Scientific publication serves as a key competence indicator, yet technical and substantive obstacles often hinder productivity. This article discusses the implementation of the "KKN In Campus" program through a workshop series organized by Puslitpen UIN Syarif Hidayatullah Jakarta. The methodology involved five intensive stages: research proposal strategy, proofreading, digital reference management, academic ethics, and journal indexation. The results indicate a significant improvement in participants' understanding of research roadmaps, proficiency in Mendeley and Zotero tools, and strategies for penetrating SINTA and Scopus-indexed journals. This program contributes strategically to building a productive and ethical academic culture.. Kata kunci : Scientific publication, reference management, journal indexation. AbstrakPengembangan profesionalisme dosen dan tenaga kependidikan, khususnya PPPK dan CPNS, merupakan elemen krusial bagi kinerja perguruan tinggi. Publikasi ilmiah menjadi indikator kompetensi utama, namun kendala teknis dan substantif sering menghambat produktivitas. Artikel ini membahas pelaksanaan program KKN In Campus melalui rangkaian workshop serial oleh Puslitpen UIN Syarif Hidayatullah Jakarta. Metode pelaksanaan mencakup lima tahap intensif: strategi proposal, proofreading, manajemen referensi digital, etika akademik, dan indeksasi jurnal. Hasil kegiatan menunjukkan peningkatan signifikan pada pemahaman peserta mengenai peta jalan riset, penguasaan tools Mendeley dan Zotero, serta strategi menembus jurnal terindeks SINTA dan Scopus. Program ini berkontribusi strategis dalam membangun budaya akademik yang produktif dan berintegritas. Kata kunci : Publikasi ilmiah, manajemen referensi, indeksasi jurnal.